2015
DOI: 10.1371/journal.pone.0121246
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Mitochondrial Dysfunction and PINK1 Are Induced by Transforming Growth Factor- Beta1 in Pulmonary Fibrosis

Abstract: BackgroundEpithelial cell death is a major contributor to fibrogenesis in the lung. In this study, we sought to determine the function of mitochondria and their clearance (mitophagy) in alveolar epithelial cell death and fibrosis.MethodsWe studied markers of mitochondrial injury and the mitophagy marker, PTEN-induced putative kinase 1 (PINK1), in IPF lung tissues by Western blotting, transmission electron microscopy (TEM), and immunofluorescence. In vitro experiments were carried out in lung epithelial cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 41 publications
3
148
0
Order By: Relevance
“…Hawkins and collaborators recently demonstrated that mutations within a surfactant protein that is linked to familial pulmonary fibrosis cause defective clearance of mitochondria (84). Studies by Patel and collaborators confirmed that PINK1-deficient mice have higher susceptibility to lung fibrosis associated with increased apoptosis (85). In addition, studies focused on lung fibroblasts demonstrated that TGF-β induces amelioration of PINK1 expression and low expression of PINK1 resulted in promotion of myofibroblast transformation (19).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…Hawkins and collaborators recently demonstrated that mutations within a surfactant protein that is linked to familial pulmonary fibrosis cause defective clearance of mitochondria (84). Studies by Patel and collaborators confirmed that PINK1-deficient mice have higher susceptibility to lung fibrosis associated with increased apoptosis (85). In addition, studies focused on lung fibroblasts demonstrated that TGF-β induces amelioration of PINK1 expression and low expression of PINK1 resulted in promotion of myofibroblast transformation (19).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
“…Controversially, TGF-β also plays a role in the regulation of damaged mitochondria-specific autophagy or mitophagy. In lung fibroblasts, TGF-β has been shown to reduce the expression of PINK1, an important modulator of mitophagy (19), yet it has the opposite effect on PINK1 expression within the lung's epithelial cells (85).…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, loss of mitochondrial biogenesis is associated with COPD, which may be associated with a significantly lower body mass index and lower muscle mass (ref. 48 and (44) PGC1-α and TFAM increased after S. aureus sepsis in the distal lung (44) Increased in ALI, pneumonia, hyperoxia (43) Increased upon S. aureus-associated sepsis (44), may be associated with resolution of lung injury (42) Increased in bronchial smooth muscle remodeling in asthma (46) Increased in lung cancer (47) Reduced in COPD, which may be associated with a significantly lower body mass index and less muscle mass (48) (53), and loss of PINK1 and defective mitophagy promote pulmonary fibrosis (PF) in animal models and in human idiopathic pulmonary fibrosis (IPF) (54,55). PF is characterized by irreversible destruction of lung architecture, abnormal wound healing, and deposition of extracellular matrix (ECM) proteins, leading to disruption of gas exchange and death from respiratory failure.…”
Section: Mitochondrial Dynamics and Biogenesismentioning
confidence: 99%
“…Mitochondria consistently play a vital role in stress responses and programmed cell death pathways. (40) Increased mROS in the PF (54) Increased in COPD (20) Increased in asthma (104) Increased in PH (108) Increased in lung cancer (106 (12) In extracellular space directly, activates inflammasome (100) Externalization during mitophagy (49) Elevated in BALF of individuals with pneumonia (12) Intratracheal injection of cardiolipin results in lower lung compliance with higher elastance and resistance (12) LYCAT altered in IPF (102).…”
Section: +mentioning
confidence: 99%